Crosstalk between the complement pathway and the contact activation system of coagulation: activated factor XI neutralizes complement factor H. - Puy, Cristina (J Immunol, 2021)
Complement factor H (CFH) is the major inhibitor of the alternative pathway of the complement system and is structurally related to beta2-glycoprotein I, which itself is known to bind to ligands including coagulation factor XI (FXI). We observed reduced complement activation when FXI activation was inhibited in a baboon model of lethal systemic inflammation, suggesting crosstalk between FXI and the complement cascade. It is unknown whether FXI or its activated form FXIa directly interacts with the complement system. We explored whether FXI could interact with and inhibit the activity of CFH. We found that FXIa neutralized CFH by cleavage of the Arg341/Arg342 bonds. FXIa reduced the capacity of CFH to enhance the cleavage of C3b by factor I (FI), and the decay of C3bBb. The binding of CFH to human endothelial cells (ECs) was also reduced after incubating CFH with FXIa. The addition of either short- or long-chain polyphosphate enhanced the capacity of FXIa to cleave CFH. FXIa also cleaved CFH that was present on ECs and in the secretome from blood platelets. The generation of FXIa in plasma induced the cleavage of CFH. Moreover, FXIa reduced the cleavage of C3b by FI in serum. Conversely, we observed that CFH inhibited FXI activation by either thrombin or FXIIa. Our study provides a novel molecular link between the contact pathway of coagulation and the complement system. These results suggest that FXIa generation enhances the activity of the complement system, and thus, may potentiate the immune response.